Pengaruh Awareness Terhadap Niat Nasabah Menggunakan Produk Perbankan Syariah pada BNI Syariah Lhokseumawe dengan Media Communication Sebagai Pemoderasi - Fuadi Fuadi; Munandar Munandar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2020)
The purpose of this study is to determine and analyze the effect of awareness on the intention to choose Islamic banking products with media communication as a moderator variable at BNI Syariah Lhokseumawe City. The location and area of research in this study to obtain primary data are in Lhokseumawe City. The population in this study is the people of Lhokseumawe city who have been customers of BNI Syariah for at least the last 3 years. The number of samples used for the study were 150 customers and were taken using an accidental technique approach. The results showed Awereness (Awareness) has a significant effect on customer intentions. Meanwhile, the findings show that media communication moderates the influence of awareness on customer intentions. Media communication in the traditional category has a greater impact than the media communication in the internet / digital category.